Congenital Syphilis in Brazil: An analysis of the epidemiological profile from 2013 to 2022 (Research, Society and Development, 2024)
Congenital Syphilis (CS) is caused by vertical transmission of Treponema pallidum and can occur at any stage of pregnancy and any phase of maternal syphilis. Early detection during prenatal care is essential to initiate treatment and prevent harm to child development. This study identifies and analyzes the variables contributing to the increasing rates of CS and aims to understand the epidemiological profile of this disease in Brazil from 2013 to 2022. An ecological, descriptive, and quantitative time-series study was conducted using data from the Department of Informatics of the Brazilian Unified Health System (DATASUS), specifically from the Notifiable of Disease Information System (SINAN) and the Live Birth Information System (SINASC), accessed via TABNET. A significant increase in CS cases was observed in Brazil, exceeding the maximum thresholds established by the World Health Organization (WHO) for acceptable incidence rates. Sociodemographic analysis revealed a higher incidence among children categorized as "brown" in demographic records, up to six days old, born to women with low educational attainment who underwent prenatal care. This scenario highlights both shortcomings in diagnostic assistance and the inadequacy of gestational syphilis treatment programs in Brazil, as cases continued to rise despite prenatal care. Social inequality emerged as a significant factor in the increasing incidence of CS, underscoring the need for fair and equitable access to healthcare services as an essential measure.